2009
DOI: 10.1007/s11999-008-0583-y
|View full text |Cite
|
Sign up to set email alerts
|

Conservative Treatment of Campanacci Grade III Proximal Humerus Giant Cell Tumors

Abstract: Level IV, therapeutic study. See the Guidelines for Authors for a complete description of levels of evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 39 publications
0
18
0
1
Order By: Relevance
“…However, to our knowledge, there is no clear definition of "more," "extensive" or "severe" destruction" in grade III GCTs and the reported indications of wide resection for GCT are also heterogeneous [5,7,22,23,30,38]. Furthermore, another dilemma of the application of the system of Campanacci et al is that some authors declared that conservative treatments instead of wide resection should be recommended for grade III GCTs [44,45]. Therefore, the role of the classifications of Enneking and Campanacci et al in planning the initial surgical treatment is limited.…”
Section: The Clinicoradiological System Of Gctmentioning
confidence: 99%
“…However, to our knowledge, there is no clear definition of "more," "extensive" or "severe" destruction" in grade III GCTs and the reported indications of wide resection for GCT are also heterogeneous [5,7,22,23,30,38]. Furthermore, another dilemma of the application of the system of Campanacci et al is that some authors declared that conservative treatments instead of wide resection should be recommended for grade III GCTs [44,45]. Therefore, the role of the classifications of Enneking and Campanacci et al in planning the initial surgical treatment is limited.…”
Section: The Clinicoradiological System Of Gctmentioning
confidence: 99%
“…The preoperative and postoperative MSTS scores were 80.04% ± 24.09% (6.67%-100.00%) and 93.19% ± 17.39% (16.67%-100.00%), respectively. Curettage is one of the most common treatment options for benign lytic bone tumors and tumorlike lesions [1][2][3][4][17][18][19]. However, after intralesional curettage of these lesions, highspeed burring, electrocautery, phenol, hydrogen peroxide, liquid nitrogen and absolute alcohol are generally advocated by many surgeons as several adjuvant treatment methods to reduce the rate of local recurrence [4,8,20,21].…”
Section: Fig6 Case 18 a 38-year-old Female Originally Was Diagnosedmentioning
confidence: 99%
“…Giant cell tumor (GCT) is known as one of the most common benign bone tumors. It is locally aggressive and sometimes may metastasize to lungs [19,24,25]. Rock et al had reported a sixfold higher risk of lung metastasis in patients who experienced local recurrence of GCT compared with patients with no history of local recurrence [24].…”
Section: Table1.clinical Details Of Patientsmentioning
confidence: 99%
See 2 more Smart Citations